Civil Law Obligations in the Financial Law Regulations A seminar at the Faculty of Law and Administration, Torun, 24 March 2015 - Mirosław Bączyk; Andrzej Borodo; Małgorzata Cilak; Tomasz Justyński; Monika Wałachowska (Prawo Budżetowe Państwa i Samorządu)
The problem, which is examined in the study, is the legal way of creation of civil law obligations. Civil law obligations are created by civil law transactions (especially by contracts). There is the question, if civil law obligations can be created directly by the legal regulations? This issue is important for the legal and financial relations between the Treasury, local government and other legal persons.